MAKNA PERILAKU PHUBBING DI KALANGAN MAHASISWA UNIVERSITAS SEBELAS MARET - Ellysya Oktaviani Ariyanti; Nurhadi Nurhadi; Yosafat Hermawan Trinugraha (Sekolah Tinggi Pariwisata Mataram, 2022)
Technology is currently experiencing very rapid development, one of which is smart phones. One of the impacts resulting from these technological developments is the phenomenon of phubbing, where people are too focused on their respective smartphones when socializing. This article aims to find out what phubbing means for phubbers when socializing. This study uses a qualitative method by providing an overview in the form of a description of the phenomenon of phubbing. Data were obtained through observation and in-depth interviews with 12 informants from each faculty at Sebelas Maret University as well as secondary data from existing literature. Then analyzed using the concept of multitasking generation. The results of the study show that with the widespread use of smartphones in various groups ranging from children to adults, phubbing is considered a normal phenomenon even though sometimes there are parties who feel offended by phubbing, especially for victims of phubbing. They feel unappreciated when interacting with their interlocutors due to being too focused on their respective smartphones.